2014
DOI: 10.12973/jesr.2014.4os12a
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between teacher autonomy and student achievement: PISA sample

Abstract: Eğitim sisteminin temel uygulayıcısı olan öğretmenlerin mesleki konularda belirli bir yetki ve özgürlük alanına sahip olmaları şeklinde tanımlanabilecek özerklik kavramı, öğretmenlerin karar verme ve öğrenciler ile ilgili konularda öngörülen mesleki seçimleri yapabilme özgürlüğü; eğitimin planlanması, geliştirilmesi ve yönetimi süreçlerine katılmaları olarak tanımlanmakta ve çalışma ortamıyla ilişkilendirilmektedir. Konuyla ilgili yapılmış çalışmalarda, daha fazla özerkliğe sahip olan öğretmenlerin, meslekleri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Of course the ultimate expectation is that achievement of students whose autonomy is supported will be high. The findings reported by Ayral et al (2014) indirectly support the finding of the current study that there is a significant relationship between teacher autonomy and learner autonomy support behaviors. Ayral et al (2014) found a positive and significant correlation between the autonomy levels of the teachers and the students' academic achievement levels.…”
Section: Results Discussion and Suggestionssupporting
confidence: 86%
See 2 more Smart Citations
“…Of course the ultimate expectation is that achievement of students whose autonomy is supported will be high. The findings reported by Ayral et al (2014) indirectly support the finding of the current study that there is a significant relationship between teacher autonomy and learner autonomy support behaviors. Ayral et al (2014) found a positive and significant correlation between the autonomy levels of the teachers and the students' academic achievement levels.…”
Section: Results Discussion and Suggestionssupporting
confidence: 86%
“…The findings reported by Ayral et al (2014) indirectly support the finding of the current study that there is a significant relationship between teacher autonomy and learner autonomy support behaviors. Ayral et al (2014) found a positive and significant correlation between the autonomy levels of the teachers and the students' academic achievement levels. Moreover, the female teachers exhibit more autonomy and learner autonomy support behaviors than male teachers and classroom teachers more than branch teachers.…”
Section: Results Discussion and Suggestionssupporting
confidence: 86%
See 1 more Smart Citation
“…Participating in the decision processes of the school (determining the content of courses, selecting textbooks, determining student discipline policies, etc.) (Ayral et al, 2014), encouragement and appreciation (Aydoğan, 2008), and supporting teacher leadership (Yılmaz et al, 2017) can positively affect teachers' autonomy behaviors, whereas if professional development is not sufficiently encouraged (TEDMEM, 2019), or if there exists a closed and/or oppressive management approach Hoy & Miskel, 2015), then it will likely negatively affect teachers' autonomy behaviors. It may be said, therefore, that teachers can feel autonomous in schools where school principals use their power resources effectively, correctly, and in a timely manner, and where teachers are given more opportunity to make certain decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are various studies examining teachers' autonomy from a theoretical base (Lundström, 2015;Öztürk, 2011;Ramos, 2006;Vangrieken et al, 2017;Wermke & Höstfält, 2014). In addition, there are many studies examining the relationship between teacher autonomy and various variables such as leadership behaviors (Yazıcı & Akyol, 2017), collaboration (Vangrieken et al, 2017), school climate , learner autonomy (Yazıcı, 2016), student achievement (Ayral et al, 2014), and job satisfaction (Çolak et al, 2017). However, the number of studies examining the relationship between teachers' autonomy and their empowerment is limited (Pearson & Moomaw, 2005).…”
Section: Introductionmentioning
confidence: 99%